IMPLEMENTASI PROGRAM ZERO WASTE EDUCATION PARK DALAM PENGELOLAAN SAMPAH: STUDI KASUS DI KOTA BATU, JAWA TIMUR - Iswara, Yoga Nur; Muchsin, Slamet; Sunariyanto, Sunariyanto (Universitas Negeri Malang, 2024)
IMPLEMENTING THE ZERO WASTE EDUCATION PARK PROGRAMME IN WASTE MANAGEMENT: A CASE STUDY IN BATU CITY, EAST JAVA This research discusses the Zero Waste Education Park Programme in Batu City, East Java, as an effort to achieve zero waste targets amidst the increasingly important issues of climate change and environmental degradation. A descriptive qualitative method with an explanatory approach was used, with primary data from interviews and secondary data from related documents. The results show that the program has various educational and waste management tools, but still faces several obstacles such as lack of socialization, lack of facilities, and technical problems with pyrolysis machines. To achieve the goal of zero waste, several strategies are recommended, including strengthening socialization, increasing community participation, improving facilities, optimising technology, enforcing regulations, economic empowerment and collaboration between different stakeholders. By implementing these strategies in an integrated and sustainable manner, it is expected that Batu City can achieve its vision of a sustainable zero-waste area and become an example for other regions in environmentally sound waste management. Penelitian ini membahas tentang Program Zero Waste Education Park di Kota Batu, Jawa Timur, sebagai upaya mencapai target bebas sampah di tengah isu perubahan iklim dan degradasi lingkungan yang semakin penting. Metode kualitatif deskriptif dengan pendekatan eksplanatif digunakan, dengan data primer dari wawancara dan data sekunder dari dokumen terkait. Hasil penelitian menunjukkan bahwa program ini memiliki berbagai wahana edukasi dan pengelolaan sampah, namun masih dihadapi oleh beberapa hambatan seperti kurangnya sosialisasi, kekurangan fasilitas, dan masalah teknis penggunaan mesin pirolisis. Untuk mencapai target zero waste, beberapa strategi direkomendasikan, termasuk penguatan sosialisasi, peningkatan partisipasi masyarakat, peningkatan fasilitas, pengoptimalan teknologi, penegakan peraturan, pemberdayaan ekonomi, dan kolaborasi antar berbagai pihak terkait. Dengan menerapkan strategi-strategi tersebut secara terpadu dan berkelanjutan, diharapkan Kota Batu dapat mencapai visi sebagai daerah zero waste yang berkelanjutan dan menjadi contoh bagi daerah lain dalam pengelolaan sampah yang ramah lingkungan.